Antigenic variation in Mycoplasma hyorhinis: increased repertoire of variable lipoproteins expanding surface diversity and structural complexity. - Rosengarten, R (1993)
VlpE is characterized as a new member in a family of variable surface lipoproteins (Vlps) of Mycoplasma hyorhinis. VlpE shows phenotypic variation in expression and size within isogenic lineages of some strains but is absent from lineages of other strains that express only three previously known Vlps. Expression of four Vlps in some cells further indicates the presence and usage of an expanded reservoir of Vlp coding sequences, which greatly increases the capacity for surface diversification.